Original paperEvaluation of the size of the placebo effect in treatments of allergic diseases and asthma based on a meta-analysis of efficacy trials of drugs - Radziwiłł, Konstanty; Kruszewski, Jerzy (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Introduction : Many methods of treatment use at least partially not only their influence on the disease mechanism but also their non-specific effects. The non-specific result of a therapy is stronger when there are more psychogenic factors in a given disease. It can be measured using both objective and subjective indicators. Many special features of allergic diseases suggest that a placebo effect may be an important factor of a total result obtained during their treatment. It also appears that a placebo effect is stronger when measurements of the effectiveness of the treatment are subjective. Material and methods : After a systematic review of the Medline database and meta-analysis of publications of results of randomized placebo -controlled efficacy trials of drugs used to treat allergic diseases and asthma (755 publications concerning 22 457 patients), and investigation of its dependence on the type of diseases and indicators used, it has been demonstrated that a placebo effect in treatments of these diseases was significantly higher (up to 40%) than in the treatment of hypertension with captopril (17%) (232 publications concerning 2 732 patients). Results : It was found that placebo had the highest share in a therapeutic effect in allergic rhinitis (57%), which differs considerably from the case of asthma (34%) and allergic skin diseases (32%). The share of the placebo effect was also significantly higher in studies in which clinical (subjective) indicators were used (59%) compared with studies using objective indicators of drug efficacy (29%).